2017
DOI: 10.1038/srep44125
|View full text |Cite
|
Sign up to set email alerts
|

Treating triple negative breast cancer cells with erlotinib plus a select antioxidant overcomes drug resistance by targeting cancer cell heterogeneity

Abstract: Among breast cancer patients, those diagnosed with the triple-negative breast cancer (TNBC) subtype have the worst prog-nosis. TNBC does not express estrogen receptor-alpha, progesterone receptor, or the HER2 oncogene; therefore, TNBC lacks targets for molecularly-guided therapies. The concept that EGFR oncogene inhibitor drugs could be used as targeted treatment against TNBC has been put forth based on estimates that 30–60% of TNBC express high levels of EGFR. However, results from clinical trials testing EGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 33 publications
3
46
0
1
Order By: Relevance
“…We designed a set of experiments to examine whether the same regulatory relationship between SRSF2 and MBD2_v2 exists in TNBC cells. First, we observed that expression of SRSF2 is, like MBD2_v2 (Bao et al ., ), subject to antioxidant‐sensitive, ROS‐regulation in TNBC cells. Using MDA‐MB‐468 and SUM149 TNBC cell lines, which expressed similarly abundant endogenous levels of SRSF2, (–)‐epicatechin antioxidant treatment reduced ROS and MBD2_v2 levels (Fig. )…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…We designed a set of experiments to examine whether the same regulatory relationship between SRSF2 and MBD2_v2 exists in TNBC cells. First, we observed that expression of SRSF2 is, like MBD2_v2 (Bao et al ., ), subject to antioxidant‐sensitive, ROS‐regulation in TNBC cells. Using MDA‐MB‐468 and SUM149 TNBC cell lines, which expressed similarly abundant endogenous levels of SRSF2, (–)‐epicatechin antioxidant treatment reduced ROS and MBD2_v2 levels (Fig. )…”
Section: Resultssupporting
confidence: 90%
“…To more directly test whether increased MBD2_v2 causes increased tumor initiation capacity, we stably overexpressed MBD2_v2 in TNBC cells prior to inoculation. We proceeded to re‐establish, as recently reported using other TNBC lines (Bao et al ., ), that MBD2_v2 overexpression promotes expansion of the CSC fraction in MDA‐MB‐231 TNBC cell cultures using a mammosphere formation assay. Stable overexpression of MBD2_v2 in cells by lentiviral transduction, confirmed by immunoblot and semiquantitative RT‐PCR analysis (Fig.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…However, some other experts considered these therapies are mostly directed towards providing temporary symptomatic relief. Thus many studies have been drifted towards approaches to mitigate this damage by supplementing antioxidant enzymes such as SOD, CAT and glutathione peroxidase [37,38], which could inhibit depolymerization of hyaluron of synovial fluid, inhibiting degradation of neutrophils and proteoglycans in articular cartilage, preventing collagen fragmentation by scavenging reactive oxidants, reducing elastase activity and inhibiting lipid peroxidation [38]. Nevertheless, various reports suggest they have poor pharmacokinetic profile that limits their use.…”
Section: Antioxidant Therapy For Autoimmune Disordersmentioning
confidence: 99%